The Appropriateness of the Design of the Structure Syllabus of the Second Semester of English Education of School of Teacher Training and Education of Universitas Muhammadiyah Surakarta - Rini Fatmawati (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
This study is aimed at describing the structure syllabus of the second semester of EnglishEducation of School of Teacher Training and Education of Universitas MuhammadiyahSurakarta in terms of the items to be taught and their sequence. The type of this study isdescriptive qualitative, the object of this study is the appropriateness of the structure syllabus ofthe second semester of English Education of School of Teacher Training and Education ofUniversitas Muhammadiyah Surakarta, the data of this study are the items to be taught in thestructure syllabus of the second semester of English Education of School of Teacher Trainingand Education of Universitas Muhammadiyah Surakarta taken from the structure curriculum ofthe second semester of English Education of School of Teacher Training and Education ofUniversitas Muhammadiyah Surakarta, and they are collected by the document analysis. Thedata are analyzed qualitatively to recognize the items to be taught based on the CourseLearning Outcomes of teaching structure to the second semester students of English Educationof School of Teacher Training and Education of Universitas Muhammadiyah Surakarta and thecriteria used as the basis of deciding them. Then, they are analyzed to recognize their sequencebased on the criteria used as the basis of deciding what sequence they have to be put. Thisstudy recognizes the appropriateness of the items to be taught in the structure syllabus of thesecond semester of English Education of School of Teacher Training and Education ofMuhammadiyah University of Surakarta, but one of them. It does not recognize theappropriateness of the sequence of the items, but one of them.Keywords: curriculum, syllabus, course learning outcome